THE INFLUENCE OF THE ENGLISH LANGUAGE ON THE RUSSIAN YOUTH SLANG - A. Izmaylova, Guzel; R. Zamaletdinova , Gulyusa; K. Zharkynbekova , Sholpan (Gênero & Direito, 2019)
This paper deals with the analysis of modern youth slang in the English language. The definition of slang attracts attention of modern philologists. Now there are a fairly large number of slang definitions that quite often contradict each other. Slang is one of the most problematic and main aspects of lexicology, as it reflects the linguistic and cultural features of the society that uses it. Students should select texts based on the language of their future specialty, make assignments for the consolidation of the passed terminology (Erofeeva & Yusupova, 2018). Today, slang is one of the most interesting language systems of modern linguistics. This paper discusses issues related to such a concept as slang, the problems of its use in spoken language of modern youth, as well as the reasons for the penetration of vocabulary into the language. In the course of studying, analysis method and questionnaires were used. Questionnaires enabled to quickly identify and interview large groups of people by a small number of sociologists. The ways of borrowing from other languages, the main ways of the formation of slang expressions were analyzed, the question of frequent use of these or those words in the spoken language of youth was also considered